2017
DOI: 10.1002/jez.2083
|View full text |Cite
|
Sign up to set email alerts
|

Thermal performance and acclimatization of a component of snake (Agkistrodon piscivorus) innate immunity

Abstract: Complement-an immune protein cascade involved in pathogen lysis-was discovered as a temperature-labile component of vertebrate plasma, yet since that time the thermal performance of complement has not received much attention from a comparative or ecological perspective. We investigated two thermal hypotheses involving the complement system of the cottonmouth snake (Agkistrodon piscivorus). We tested whether complement performance would conform to optimal thermal reaction norms commonly observed in ectotherm ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 65 publications
1
22
0
Order By: Relevance
“…These data show that the area of maximal serum complement efficiency fall within the preferred temperature range of C. viridis (28-32°C) (Gannon & Secoy, 1985). Similar results have been noted in cottonmouths (A. piscivorus; Graham et al, 2017) and corn snakes (Pantherophis guttatus; Stahlschmidt, French, Ahn, Webb, & Butler, 2017). It is interesting to note the wide thermal range at which maximum activity was observed.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These data show that the area of maximal serum complement efficiency fall within the preferred temperature range of C. viridis (28-32°C) (Gannon & Secoy, 1985). Similar results have been noted in cottonmouths (A. piscivorus; Graham et al, 2017) and corn snakes (Pantherophis guttatus; Stahlschmidt, French, Ahn, Webb, & Butler, 2017). It is interesting to note the wide thermal range at which maximum activity was observed.…”
Section: Discussionsupporting
confidence: 82%
“…More recently, Sparkman and Palacios (2009) showed that garter snakes (Thamnophis elegans) exhibit strong innate immunity in the form of antibacterial activity of plasma, high serum complement titer, and natural antibody production. Additionally, cottonmouths (Agkistrodon piscivorus) show a strong positive correlation between temperature and complement performance (Graham, Fielamn, & Mendonça, 2017). Here, we provide a detailed characterization of serum complement activation in the plasma of the prairie rattlesnake (Crotalus viridis).…”
Section: Introductionmentioning
confidence: 97%
“…Plasma was separated and stored at −80°C until shipment on dry ice to Stockton University where the assays were conducted. Innate immune function was assessed using a plasma bacteriakilling assay (Tieleman et al, 2005), which primarily tests the ability of complement proteins to kill live Escherichia coli (Baker and Merchant, 2018;Graham et al, 2017;Merchant et al, 2003). Briefly, one pellet of E. coli (ATCC #8739; Microbiologics, St Cloud, MN, USA) was suspended in 40 ml sterile PBS.…”
Section: Assessment Of the Immune Responsementioning
confidence: 99%
“…The ectotherm immune system relies on the temperature-dependent activity of enzymes and cells, and immune performance is therefore also constrained by temperature. Although the number of studies on the thermal performance of the ectotherm immune system is limited, immune activity generally conforms to a classic thermal performance curve and operates over a wide range of temperatures (Butler et al, 2013;Ferguson et al, 2016;Graham et al, 2017;Murdock et al, 2012;Zimmerman et al, 2017).…”
Section: Thermal Dependence Of Ectotherm Immunitymentioning
confidence: 99%